2002
DOI: 10.1126/science.1071163
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Biogenesis in Skeletal Muscle by CaMK

Abstract: Endurance exercise training promotes mitochondrial biogenesis in skeletal muscle and enhances muscle oxidative capacity, but the signaling mechanisms involved are poorly understood. To investigate this adaptive process, we generated transgenic mice that selectively express in skeletal muscle a constitutively active form of calcium/calmodulin-dependent protein kinase IV (CaMKIV*). Skeletal muscles from these mice showed augmented mitochondrial DNA replication and mitochondrial biogenesis, up-regulation of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
467
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 595 publications
(502 citation statements)
references
References 23 publications
23
467
1
6
Order By: Relevance
“…(12) In addition, several signal transduction pathways that regulate PGC1a expression independent of changes in intracellular cGMP levels have also been described. (2,6,7,13) Do the data in the present experiments support the contention that the observed NO effects on PGC1a expression are transduced exclusively through a sGC-sensitive, cGMP-dependent signaling pathway? Some insight into this question comes from their studies on the human monocytic cell line U937.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…(12) In addition, several signal transduction pathways that regulate PGC1a expression independent of changes in intracellular cGMP levels have also been described. (2,6,7,13) Do the data in the present experiments support the contention that the observed NO effects on PGC1a expression are transduced exclusively through a sGC-sensitive, cGMP-dependent signaling pathway? Some insight into this question comes from their studies on the human monocytic cell line U937.…”
Section: Introductionsupporting
confidence: 67%
“…Signal transduction pathways that modulate mitochondrial biogenesis through the control of PGC1a expression in mammalian tissues. (1,2,4,6,7,13,23) Changes in the levels or ratio of metabolic indices [blue boxes] are sensed by specific protein-modifying enzymes (i.e., kinases, phosphatases). These proteins in turn activate diverse signaling cascades [gold circles] that ultimately affect the expression of PGC1a [pink oval].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Calcium signalling modulates mitochondrial biogenesis through the calcium/calmodulin-dependent protein kinase II (CaMKII), p38 mitogen activated protein kinase (MAPK) and PGC-1α. 19,20 Although, no clear PGC-1a homolog is present in the nematode genome, we found that SKN-1 activity is modulated by cytoplasmic calcium levels via the CaMKII homolog, UNC-43, upon mitochondrial dysfunction.…”
mentioning
confidence: 73%
“…Ppara is centrally involved in mitochondrial biogenesis and fatty acid oxidation [6]. Increased production of Ppargc1a, a key regulator of mitochondrial biogenesis, may be involved in obesity and the pre-diabetic state in skeletal muscle [7]. Therefore, regulating Pparg/a activity and adipocyte metabolism may improve insulin sensitivity and glucose disposal [2,5,8].…”
Section: Introductionmentioning
confidence: 99%